Clinical comparison between three regional analgesic modalities using ultrasound guidance for postoperative pain relief in children undergoing unilateral lower abdominal surgery - Mostafa M Sabra; Usama I Abotaleb (Wolters Kluwer Medknow Publications, 2019)
Objective Many regional techniques have been developed as safe and practical methods for adequate postoperative analgesia for unilateral lower abdominal surgery in children. The aim of the study was to compare the effectiveness of analgesia by using quadratus lumborum (QL) block, transversus abdominis plane (TAP) block, and caudal analgesia in children undergoing unilateral lower abdominal surgery. Patients and methods This prospective, randomized, single-blinded study was conducted at Al-Hussein Hospital. Two hundred and forty pediatric patients aged 2-7 years were enrolled to undergo lower abdominal surgeries and were allocated into four groups (60 each). Group A : received QL block, group B: received TAP block, group C: received caudal block, with ultrasound guidance in the three groups, and group D: the control group. The primary outcome was postoperative pain control which was assessed by using Children's Hospital Eastern Ontario Pain Scale and objective pain score. Intraoperative hemodynamics, postoperative complication, satisfaction of the parents, and postoperative analgesic requirements were the secondary outcomes. Results There was no significant difference between groups in mean intraoperative arterial blood pressure and heart rate. There was significant difference between groups A and C in pain scores assessment (P<0.05), but no significant difference between groups A and B. Postoperative analgesia requirements were significantly higher in group B compared with group A (P<0.05). Parent satisfaction was markedly observed in groups A and B. Conclusion This study's outcomes demonstrated that for pediatric patients who are experiencing unilateral lower abdominal surgery, QL block and TAP block under ultrasound guidance proved to be safe with no recorded complications either intra- or postoperatively, with QL block superiority as evidenced by decreased rescue postoperative analgesia and lower pain scores. The QL block offered more effective for postoperative analgesia than the TAP block and caudal block.